V drobovju liberalne demokracije - Pikalo, Jernej (Teorija in praksa, 1997)
The author deals with the issues of liberal democracy as a form of rule and level of 158 consciousness. He states that liberal democracy cannot be appliedonto any cultural preconditions as is the general opinion in the western civilised sphere. The first part of the paper presents some basic accentuations and tensions deriving from the hybrid concept of liberal democracy itself. The second part is focused on cultural preconditions, which, according to the author, signify a major obstacle in the implementation of the global rule of liberal democracy. The author deals with the issues of liberal democracy as a form of rule and level of 158 consciousness. He states that liberal democracy cannot be appliedonto any cultural preconditions as is the general opinion in the western civilised sphere. The first part of the paper presents some basic accentuations and tensions deriving from the hybrid concept of liberal democracy itself. The second part is focused on cultural preconditions, which, according to the author, signify a major obstacle in he implementation of the global rule of liberal democracy.
Keywords: liberalna demokracija; liberalism; liberalizem; politična kultura; konfucianizem